Production of secondary metabolites through glycerol fermentation under carbon‐excess conditions by the yeasts Yarrowia lipolytica and Rhodosporidium toruloides. Issue 9 (10th April 2017) - Papanikolaou, Seraphim; Kampisopoulou, Eleni; Blanchard, Fabrice; Rondags, Emmanuel; Gardeli, Chryssavgi; Koutinas, Apostolis A.; Chevalot, Isabelle; Aggelis, George
Abstract : The biochemical behavior of the yeasts Rhodosporidium toruloides DSM 4444, Yarrowia lipolytica ACA YC 5029, and Y. lipolytica ACA YC 5030 was evaluated on waste glycerol‐based media, added at increasing initial concentrations (50–140 g/L), with nitrogen remaining constant. During flask cultivation of Y. lipolytica ACA‐YC 5030, and although medium pH remained >4.8, major metabolites were the polyols mannitol (CMl) and erythritol (CEr) (CMlmax = 32.1 g/L, conversion yield per glycerol consumed =0.23 g/g, and CErmax = 35.5 g/L, yield ≈0.25 g/g). For the strain ACA‐YC 5029, equally in flasks and pH >4.8, the major metabolites were again mannitol and erythritol, with CMlmax = 28.9 g/L (conversion yield ≈0.21 g/g), and CErmax = 33.6 g/L (yield ≈0.24 g/g). In contrast, in batch‐bioreactor experiment, the yeast ACA YC‐5029 produced mainly citric acid (maximum concentration =39 g/L, yield on glycerol =0.42 g/g). R. toruloides DSM 4444 was flask‐cultured at increasing initial glycerol quantities (up to ≈140 g/L) and displayed significant growth producing also satisfactory amounts of lipids. The maximum DCW concentration achieved was 39.1 g/L. Maximum lipids were 13.7 g/L (at that point lipid in DCW was 37.0% w/w). The major cellular fatty acid produced was oleic acid. Phospholipids of R. toruloides were the most unsaturated fraction among lipid fractions quantified. Practical applications: Industrial glycerol, the main by‐product of biodiesel‐producing facilities, appears in constantly increasing quantities in the market volume due to the worldwide rise of biodiesel production, rendering the valorization of this by‐product as a very important scientific priority. In this report, the yeasts Y. lipolytica ACA YC 5029 and Y. lipolytica ACA YC 5030 were cultivated in submerged batch experiments with industrial glycerol as substrate under nitrogen limitation and appreciable quantities of mannitol and erythritol, compounds presenting significant importance for the food industries, were synthesized. The yeast R. toruloides DSM 4444, equally batch‐cultured on glycerol under nitrogen limitation, produced appreciable quantities of biomass that contained high concentrations of microbial lipids, that could be transformed into "2nd generation" biodiesel. The current study, hence, provides viable possibilities of glycerol valorization through its use as substrate in order metabolic compounds of added‐value to be synthesized. Crude glycerol, the principal "waste" stream deriving from biodiesel production process, is converted with the aid of microbial fermentations into secondary metabolites useful for the food‐ and biofuels‐producing industries. The metabolic compounds synthesized are microbial lipids (single cell oils) amenable to be converted into 2nd generation biodiesel with fermentations led by a strain of the yeast Rhodosporidium toruloides and mannitol, erythritol and citric acid with fermentations led by strains of the yeast Yarrowia lipolytica . Abstract : Crude glycerol, the principal "waste" stream deriving from biodiesel production process, is converted with the aid of microbial fermentations into secondary metabolites useful for the food‐ and biofuels‐producing industries. The metabolic compounds synthesized are microbial lipids (single cell oils) amenable to be converted into 2nd generation biodiesel with fermentations led by a strain of the yeast Rhodosporidium toruloides and mannitol, erythritol and citric acid with fermentations led by strains of the yeast Yarrowia lipolytica .